PENGARUH CITRA DESTINASI DAN E-WOM TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN NUSANTARA KE PULAU LIHAGA, SULAWESI UTARA - Wenur, Hana Fabiola; Agus Wikanatha Sagita, Putu; Kristianto, Yohanes (Jurnal IPTA (Industri Perjalanan Wisata); Vol 11 No 2 (2023): Jurnal IPTA (December 2023)DO - 10.24843/IPTA.2023.v11.i02.p11, 2023)
The background of this research is to find out the influence of destination image and E- WOM on Domestic Tourist Visit Decision to Lihaga Island, North Sulawesi. Determination of the sample in this study used a purposive sampling method with a total sample of 100 respondents. The data collection used the distribution of questionnaires online through social media, observation, literature study, and documentation. The techniques used in this research are descriptive quantitative with validity test, reliability test, classical assumption test, multiple linear regression analysis, t-test, f- test, and coefficient of determination test. For the tool used for the implementation of this data analysis test is IBM SPSS statistics 25. The results of this study indicate that destination image does not significantly influence the visit decision, while E-WOM has a significant effect on visit decision. The results of this study are destination image and E-WOM done simultaneously has an influence on domestic tourist visit decisions. The results of coefficient determination (Rsquare) is 60%.